Kelayakan Usaha Ternak Burung Puyuh di Kecamatan Prambon Kabupaten Nganjuk - Ta’wim, Akhris Asanit; Artini, Widi; Andajani, Wiwiek; Nina Lisanty (Universitas Kadiri, 2024)
Prambon District in Nganjuk Regency, East Java, has shown its community's adaptation to the COVID-19 pandemic by switching to livestock businesses, significantly raising quail. With mostof the population initially working as farmers, the Work From Home (WFH) policy and Large-Scale Social Restrictions (PSBB) encouraged the Prambon community to choose livestock as an additional source of income. Research in Mojoagung Village involving 23 breeders showed that raising quail in Prambon has promising economic potential. Even though production costs reach IDR33,704,380 for 1000 quails, the net income from selling quail eggs reaches IDR77,220,620 during the production period. Additional income from selling quail meat and quail dung (fertilizer) reached IDR2,250,000 and IDR1,575,000 respectively. This livestock business is profitable and very worthy of development. Policy implications involve government support in the form of training, technical assistance, and market development to support local economic growth and diversification of livelihoods, making quail farming a sustainable option to improve the welfare of the Prambon community. Kecamatan Prambon di Kabupaten Nganjuk, Jawa Timur, menunjukkan adaptasi masyarakatnya terhadap pandemi COVID-19 dengan beralih ke usaha peternakan, terutama beternak burung puyuh. Dengan mayoritas penduduk yang awalnya berprofesi sebagai petani, kebijakan Work From Home (WFH) dan Pembatasan Sosial Berskala Besar (PSBB) mendorong masyarakat Prambon untuk memilih usaha peternakan sebagai sumber pendapatan tambahan. Penelitian di Desa Mojoagung melibatkan 23 peternak menunjukkan bahwa beternak burung puyuh di Prambon memiliki potensi ekonomi yang menjanjikan. Meskipun biaya produksi mencapai Rp33.704.380 untuk 1000 ekor burung puyuh, pendapatan bersih dari penjualan telur puyuh mencapai Rp77.220.620 selama masa produksi. Pendapatan tambahan dari penjualan daging puyuh dan kotoran puyuh (pupuk) masing-masing mencapai Rp2.250.000 dan Rp1.575.000. Usaha ternak ini menguntungkan dan sangat layak untuk dikembangkan. Implikasi kebijakan melibatkan dukungan pemerintah dalam bentuk pelatihan, bantuan teknis, serta pengembangan pasar untuk mendukung pertumbuhan ekonomi lokal dan diversifikasi mata pencaharian, menjadikan beternak burung puyuh sebagai opsi yang berkelanjutan untuk meningkatkan kesejahteraan masyarakat Prambon.